Towards a sustainable district: a streamlined Life cycle assessment applied to an Italian urban district. (August 2019) - Palumbo, E; Traverso, M; Antonini, E; Boeri, A
Abstract: The literature shows a lack of environmental indicators able to support the transition from a sustainable to a smart city framework, since the priority area "built environment" is indeed more comprehensively addressed by urban sustainability assessment systems (13%), than by smart city frameworks (4%) [12]. As "smaller cities inside a larger agglomerate" [19], urban districts play a key role in defining effective and innovative paths toward a smarter city, but defining a sustainable urban district is not straightforward, and even less is capturing the induced impacts due to interactions between individual buildings and their surround urban setting [23]. The adoption of a quantitative method for evaluation, such as Life Cycle Assessment (LCA), emerges as an essential step for this purpose [24]. This article explores the application of a streamlined LCA on the urban district main issues (buildings, energy, water and waste), referring to an urban retrofitting intervention of Bolognina neighbourhood. A set of mitigation strategies developed by an interdisciplinary research group (joining researcher team from the Department of Architecture of the University of Bologna and Institute of Sustainability in Civil Engineering of the RWTH Aachen University) provides the reference framework for the application deepened within the article. This work is a first application of LCA to a case study but it not includes a comprehensive sustainability framework yet, further activities are planned to finalize the analysis, e.g. taking account of social dimension by applying Social Life Cycle Assessment.